Cooperative interaction of interferon regulatory factor -1 and bromodomain—containing protein 4 on RNA polymerase activation for intrinsic innate immunity - Xu, Xiaofang; Qiao, Dianhua; Brasier, Allan R. (Frontiers in Immunology, 2024)
The human orthopneumovirus, Respiratory Syncytial Virus (RSV), is the causative agent of severe lower respiratory tract infections (LRTI) and exacerbations of chronic lung diseases. In immune competent hosts, RSV productively infects highly differentiated epithelial cells, where it elicits robust anti-viral, cytokine and remodeling programs. By contrast, basal cells are relatively resistant to RSV infection, in part, because of constitutive expression of an intrinsic innate immune response (IIR) consisting of a subgroup of interferon (IFN) responsive genes. Here, we use human small airway epithelial cell hSAECs as a multipotent airway stem cell model to examine regulatory control of an intrinsic IIR pathway. We find hSAECs express patterns of intrinsic IIRs, highly conserved with pluri-and multi-potent stem cells. We demonstrate a core intrinsic IIR network consisting of Bone Marrow Stromal Cell Antigen 2 (Bst2), Interferon Induced Transmembrane Protein 1 (IFITM1) and Toll-like receptor (TLR3) expression are directly under IRF1 control. Moreover, expression of this intrinsic core is rate-limited by ambient IRF1• phospho-Ser 2 CTD RNA Polymerase II (pSer2 Pol II) complexes binding to their proximal promoters. In response to RSV infection, the abundance of IRF1 and pSer2 Pol II binding is dramatically increased, with IRF1 complexing to the BRD4 chromatin remodeling complex (CRC). Using chromatin immunoprecipitation in IRF1 KD cells, we find that the binding of BRD4 is IRF1 independent. Using a small molecule inhibitor of the BRD4 acetyl lysine binding bromodomain (BRD4i), we further find that BRD4 bromodomain interactions are required for stable BRD4 promoter binding to the intrinsic IIR core promoters, as well as for RSV-inducible pSer2 Pol II recruitment. Surprisingly, BRD4i does not disrupt IRF1-BRD4 interactions, but disrupts both RSV-induced BRD4 and IRF1 interactions with pSer2 Pol II. We conclude that the IRF1 functions in two modes-in absence of infection, ambient IRF1 mediates constitutive expression of the intrinsic IIR, whereas in response to RSV infection, the BRD4 CRC independently activates pSer2 Pol II to mediates robust expression of the intrinsic IIR. These data provide insight into molecular control of anti-viral defenses of airway basal cells.